2020
DOI: 10.24953/turkjped.2020.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation in patients with 17 α-hydroxylase deficiency caused by a deletion in the CYP17A1 gene: short stature

Abstract: Background. Patients with 17α-hydroxylase deficiency (17 OHD) usually present with tall stature and eunuchoid features, rather than growth retardation. However, unlike the classic form of the disease, short stature due to a lack of pubertal growth spurt and sex hormone deficiency was present in our four cases. We wanted to emphasize that short stature might be the cause of first presentation in patients with 17 OHD. Cases. We report five patients of Kurdish origin with 17 OHD, four of whom had short stature; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The MLPA method is mainly employed in the molecular diagnosis of CAH owing to 21hydroxylase deficiency for the detection of deletions/ duplications in CYP21A2. There are few studies on the application of MLPA in the diagnosis of 17OHD [12][13][14]. The present case illustrates the need for scrutinizing a homozygous mutation pattern by not only direct DNA sequencing but also MLPA analysis.…”
Section: Discussionmentioning
confidence: 78%
“…The MLPA method is mainly employed in the molecular diagnosis of CAH owing to 21hydroxylase deficiency for the detection of deletions/ duplications in CYP21A2. There are few studies on the application of MLPA in the diagnosis of 17OHD [12][13][14]. The present case illustrates the need for scrutinizing a homozygous mutation pattern by not only direct DNA sequencing but also MLPA analysis.…”
Section: Discussionmentioning
confidence: 78%
“…The MLPA test is a reliable and convenient method for diagnosing large deletions/duplications and is commonly used when large sets of samples need to be tested in a single run. In different studies conducted in Turkey, it has been reported that exon 1-6 deletion of the CYP17A1 gene may cause a serious phenotypic change by severely disrupting P450c17 enzyme activity, especially in natives from the eastern and southeastern regions of Turkey [Turkkahraman et al, 2015;Kardelen et al, 2018;Bolu et al, 2020;Beştaş et al, 2021]. These results suggest that exon 1-6 deletion is a founder mutation in east and southeast Turkey.…”
Section: Discussionmentioning
confidence: 97%